Development of a framework for High-Performance Political Regimes (HPPR) - อภิบาลศรี อัญญรัตน์ (วารสารพัฒนาสังคมและยุทธศาสตร์การบริหาร, 2023)
Thailand has adhered to a democratic parliamentary system since the 1932 regime change, but the ethical problems of politicians are from politicians seeking personal advantage rather than the public. There is corruption and use of powers by the parties irrespective of the public interest and consequences. Thai society has demands against politicians in terms of vision, knowledge, ability, morality, and responsibility to the country. In particular, politicians must not corrupt. People have the right to select politiciants to be their representatives. However, they are not good at knowing all the applicants. Therefore, a high-performance political regime has been proposed. Beginning from the selection, assessment, development, and retention of high-performing politicians in political regimes to build the capacity of the nation’s growth so that it can compete with globalization while genuinely promoting the well-being of its citizens